2012
DOI: 10.5345/jkibc.2012.12.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PMIS Quality on Intention to Use and User Satisfaction

Abstract: Establishing a success model of a specific information system is critical to understanding the mechanism of IS success, the various dimensions of IS performance, and the factors and their causal relations in IS success. As one of the key IT applications, the project management information system (PMIS), particularly the web-based PMIS (Web-PMIS), has played a significant role in construction management processes in Korea. However, there have been few research attempts made to construct a Web-PMIS success model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…This process ensures the system meets the goals and requirements to validate that the product desired by the user has been developed. Previous research indicated successful application of PMIS's heavy reliance on the factors of user intentions and user satisfaction (Sung et al 2012). Thus, most PMIS developers significantly improved system architecture and user interface.…”
Section: Software Validation Methodsmentioning
confidence: 99%
“…This process ensures the system meets the goals and requirements to validate that the product desired by the user has been developed. Previous research indicated successful application of PMIS's heavy reliance on the factors of user intentions and user satisfaction (Sung et al 2012). Thus, most PMIS developers significantly improved system architecture and user interface.…”
Section: Software Validation Methodsmentioning
confidence: 99%
“…기존 PMIS 관련 연구는 ASP방식 PMIS 기능적 문제점 분석을 통한 기능개선 방안을 제시하는 연구가 많이 진행 되어 왔지만 이를 실제 시스템에 적용한 연구는 부족한 편이며 [6,7], 또한 PMIS 품질이 사용자에게 미치는 영향 을 분석하여 이를 시스템에 적용하여 개선방안을 제시하 는 연구도 진행되어왔다 [8]. 최근에는 모바일 PMIS 모듈 을 개발하는 연구가 진행 중이나 여러 가지 모듈을 탑재 한 것이 아닌 단일 모듈로 구성된 시스템 개발에 한정되 어 있으며 [9], 또한 PMIS에 BIM을 결합하여 진도관리 및 가상현실을 통한 공사관리를 할 수 있는 연구를 통한 공 사관리 시스템 개발을 진행 중이다 [10,11,12].…”
Section: 기존 연구의 한계점unclassified